Bridge to Terabithia - Paterson, Katherine; Diamond, Donna (New York : Crowell, 1977)
The life of a ten-year-old boy in rural Virginia expands when he becomes friends with a newcomer who subsequently meets an untimely death trying to reach their hideaway, Terabithia, during a storm.
"A Harper Trophy book."
Booklist
Keywords: Friendship -- Fiction; Death -- Fiction; Newbery Medal books